The measurement of intrametropolitan geo-economic space in South Africa: The PWV as an example - Geyer, HS; Steyn, HS (Town and Regional Planning, 1989)
An attempt has been made to develop an economic potential model to facilitate the analysis of the geo-economic space in and around development centres in South Africa. The PretoriaWitwatersrand-Vaal Triangle area is used as an example to illustrate the quantification of economic potential maps in this study. It is a geometrical model which indicates the geographical extent of gradually changing levels of economic potential, based on economic indicators consisting of population, labour, and income variables. As a normative model, it offers the planner the opportunity of an objective comparison of areas which in terms of development criteria may differ greatly from one another, and as such constitutes an instrument which can be used in conjunction with other conventional research results in the formulation of development policies in the formal economic sector on a regional and supra-regional level.